If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying onehalf + -2 = onesixthf Reorder the terms: -2 + aefhlno = onesixthf Solving -2 + aefhlno = efhinostx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + aefhlno = 2 + efhinostx Combine like terms: -2 + 2 = 0 0 + aefhlno = 2 + efhinostx aefhlno = 2 + efhinostx Divide each side by 'efhlno'. a = 2e-1f-1h-1l-1n-1o-1 + il-1stx Simplifying a = 2e-1f-1h-1l-1n-1o-1 + il-1stx
| m/0.3=8 | | w/4+13=21 | | 8Q=24-P | | 2x+4=4x-3 | | 360-x^2-x^2/2=3x | | w/4+13=24 | | 5(a-3)+2a=27 | | 3(4)-6y=6 | | x+y/2=65 | | x-(-17)= | | 3/4x+7=19 | | 1/3(12-6r)= | | x-17= | | 5(a-3)+3m=27 | | (48-12)/4.5=X | | 2a+3(a+4)=-3 | | 2+3a-7= | | x+9=2x-44 | | -5+6a+3=34 | | -x+1/2y-2=0 | | x^2(x+3)=70 | | -9-7x=23 | | 3x^2+x^2=70 | | 4/9(18-9t)= | | 3a-5-2a=-9 | | 1996+43B=7385-67B | | 495+15x=720 | | (2gk+4)=(5-h) | | 3[x]=12 | | 3(6)-6y=6 | | 14-x/5=x/2 | | (5-h)=(2gk+4) |